Sociopatologije vsakdanjosti: anorexia nervosa - Rener, Tanja (Družboslovne razprave, 1998)
Anorexia nervosa is interpreted in social theory in different ways: as a pathological crystalisation of culture, as social manipulation of (female) bodies, as an example of power relations between the sexes etc. At the same time, anorexia embodies the current discussions on contemporary identities as it represents an example of failed identity struggle. Anorexia means a search for individualisation and authonomy in the (middle class) family where "the common family meal" has a specific symbolic dimension. The anorexic's struggle for identity is thus dangerous for it attacks the common table as the very heart of this symbol and shows what in every normal family should remain hidden, namely, that family relations mean also power relations and an oppression of the weak members in a masquerade of a love which smothers.
Keywords: social psychology; socialna psihologija; družina; family; woman; ženske; individualizacija; identiteta; kvaliteta življenja; prehrana; food; sociologija prehrane; prehranjevalne motnje; anoreksija